An Energy-Aware Framework for Reliable and Secure End-to-End Ubiquitous Data Communications - Castiglione, Arcangelo; De Santis, Alfredo; Castiglione, Aniello; Palmieri, Francesco; Fiore, Ugo (2013 5th International Conference on Intelligent Networking and Collaborative Systems, 2013)
Despite the wide deployment of beyond 3G cellular networks and high capacity Wi-Fi coverage infrastructures, finding the best way for achieving ubiquitous and secure mobile data transfer services in everyday's life activities, it is still an open question. In particular, security becomes a key factor in such a scenario, since a large number of mobile terminal devices (smartphones, handhelds, tablets) simultaneously supporting multiple networking technologies, may be used to store, access, manipulate, or communicate sensitive data from everywhere and at any time. However, the computational efforts required for achieving security, due to the inherent complexity of cryptographic algorithms, heavily affect the power consumption of the involved terminals. Such energy demand, together with the amount of power already required to manage the communication activities carried out by using multiple network interfaces, make energy efficient secure communication among mobile hardware-constrained handheld devices, a really challenging topic. Based on above considerations, we present the architecture of a framework which enables secure end-to-end and reliable data transfer for heterogeneous mobile terminals by also describing and modeling its power demand, with the aim of achieving a robust and reliable ubiquitous data transfer service also minimizing the overall battery consumption in such devices.